Peran Instagram Sebagai Pemasaran Media Sosial Dalam Membangun Kesadaran Merek dan Dampaknya terhadap Keputusan Pembelian pada Salah Satu Kedai Kopi Lokal Top Brand Indonesia - Marie, Andhalia Liza; Widodo, Rintis Eko; Prasetio, Arton Briyan (Jurnal Ilmiah Pariwisata; Vol 28 No 3 (2023): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v28i3.1752, 2023)
The purpose of this research is to determine how brand awareness mediates the influence of social media marketing on purchasing decisions. The sampling technique in this research is non-probability sampling with a purposive sampling method. Data was taken using Google Form with a total of 138 respondents. The data analysis technique used is PLS-SEM. The results of this research state that: (1) Social media marketing has a positive effect on brand awareness; (2) Brand awareness has a positive effect on purchasing decisions; (3) Social media marketing has a positive effect on purchasing decisions; (4) Brand awareness mediates the influence of social media marketing on purchasing decisions. Social media marketing positively influences brand awareness through reaching a wide audience, and visual content. High brand awareness positively influences purchasing decisions by increasing consumer familiarity, trust and preference. Brand awareness also acts as a link between social media marketing and purchasing decisions through creating positive perceptions and better knowledge about the brand, playing a key role in influencing consumer purchasing actions. Keywords: Social Media Marketing, Brand Awareness, Purchase Decisions